Informational pathologies and interest bubbles: Exploring the structural mobilization of knowledge, ignorance, and slack. (March 2018) - Wiewiura, Joachim S; Hendricks, Vincent F
This article contends that certain configurations of information networks facilitate specific cognitive states that are instrumental for decision and action on social media. Group-related knowledge and belief states—in particular common knowledge and pluralistic ignorance—may enable strong public signals. Indeed, some network configurations and attitude states foster informational pathologies that may fuel interest bubbles affecting agenda-setting and the generation of narratives in public spheres.